Antihypertensive and cardioprotective effects of the dipeptide isoleucine–tryptophan and whey protein hydrolysate. (22nd September 2015) - Martin, M.; Kopaliani, I.; Jannasch, A.; Mund, C.; Todorov, V.; Henle, T.; Deussen, A.
Abstract: Aims: Angiotensin‐converting enzyme inhibitors are treatment of choice in hypertensive patients. Clinically used inhibitors exhibit a structural similarity to naturally occurring peptides. This study evaluated antihypertensive and cardioprotective effects of ACE‐inhibiting peptides derived from food proteins in spontaneously hypertensive rats. Methods and Results: Isoleucine–tryptophan ( in vitro IC50 for ACE = 0.7 μ m ), a whey protein hydrolysate containing an augmented fraction of isoleucine–tryptophan, or captopril was given to spontaneously hypertensive rats ( n = 60) over 14 weeks. Two further groups, receiving either no supplement (Placebo) or intact whey protein, served as controls. Systolic blood pressure age‐dependently increased in the Placebo group, whereas the blood pressure rise was effectively blunted by isoleucine–tryptophan, whey protein hydrolysate and captopril (−42 ± 3, −38 ± 5, −55 ± 4 mm Hg vs. Placebo). At study end, myocardial mass was lower in isoleucine–tryptophan and captopril groups but only partially in the hydrolysate group. Coronary flow reserve (1 μ m adenosine) was improved in isoleucine–tryptophan and captopril groups. Plasma ACE activity was significantly decreased in isoleucine–tryptophan, hydrolysate and captopril groups, but in aortic tissue only after isoleucine–tryptophan or captopril treatment. This was associated with lowered expression and activity of matrix metalloproteinase‐2. Following isoleucine–tryptophan and captopril treatments, gene expression of renin was significantly increased indicating an active feedback within renin–angiotensin system. Conclusion: Whey protein hydrolysate and isoleucine–tryptophan powerfully inhibit plasma ACE resulting in antihypertensive effects. Moreover, isoleucine–tryptophan blunts tissue ACE activity, reduces matrix metalloproteinase‐2 activity and improves coronary flow reserve. Thus, whey protein hydrolysate and particularly isoleucine–tryptophan may serve as innovative food additives with the goal of attenuating hypertension.